(untitled) (Theatrum historiae, 2012)
This article deals with the residences of Orava and Liptov regional officers in 17 and 18 centu- ries. Regarding the administration, Hungary was divided into larger and smaller regional units called counties (in Slovak stolica / župa, in German Komitat). The administration of these units was in the hands of officers (vice-chair, notary, treasury, fiscal and serviceman), who recruited from the local aristocrats and landlords, i.e. the local elites. The functions in the administration meant a constant income of financial cash from the annual salary or the fees for the preparation of written deeds not related to the exercise of the office. The officers then presented the acquired social status in their residences – castles and smaller knight manors called curia. The acquired status was also manifested less visibly in the form of establishing close kin relations between the officers.